2021
DOI: 10.3390/ma14185394
|View full text |Cite
|
Sign up to set email alerts
|

Facile Microwave Hydrothermal Synthesis of ZnFe2O4/rGO Nanocomposites and Their Ultra-Fast Adsorption of Methylene Blue Dye

Abstract: The industry development in the last 200 years has led to to environmental pollution. Dyes emitted by pharmaceutical and other industries are major organic pollutants. Organic dyes are a pollutant that must be removed from the environment. In this work, we adopt a facile microwave hydrothermal method to synthesize ZnFe2O4/rGO (ZFG) adsorbents and investigate the effect of synthesis temperature. The crystal structure, morphology, chemical state, and magnetic property of the nanocomposite are investigated by X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 113 publications
(143 reference statements)
2
4
0
Order By: Relevance
“…Furthermore, average crystal sizes were increased with RGO doping, which was calculated by the Scherrer equation ( Patterson, 1939 ) . XRD results show the successful synthesis of the ZnFe 2 O 4 /RGO NCs, which agrees with previous studies ( Kaur et al, 2018 , Wang and Shih, 2021 ). As shown in the SEM image, ZnFe 2 O 4 NPs displayed uniform distributions of spherical particles with agglomerations ( Sripriya et al, 2018 ) .…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, average crystal sizes were increased with RGO doping, which was calculated by the Scherrer equation ( Patterson, 1939 ) . XRD results show the successful synthesis of the ZnFe 2 O 4 /RGO NCs, which agrees with previous studies ( Kaur et al, 2018 , Wang and Shih, 2021 ). As shown in the SEM image, ZnFe 2 O 4 NPs displayed uniform distributions of spherical particles with agglomerations ( Sripriya et al, 2018 ) .…”
Section: Discussionsupporting
confidence: 92%
“…In Figure 6B, the TEM morphology of ZnFe 2 O 4 revealed moderate aggregation of primarily particles with counted particle sizes (n = 22) of 14.30 ± 4.34 nm, which is less than that suggested by SEM. Such structural morphology of ZnFe 2 O 4 was also seen by Abbasian et al [36], and the particle sizes are close to that reported by Wang and Shih (12.1 nm) [43]. Figure 6C shows TEM image of ZFAC nanocomposite in which a relatively uniform distribution of metal oxide nanoparticles on the AC surface can be observed.…”
Section: Tem Analysissupporting
confidence: 87%
“…In optimum conditions of pH = 8, initial concentration = 10 mg L −1 , adsorbent dose = 10 mg, reaction time = 30 min and temperatur = 298 K, the removal efficiency of 98% was achieved. The results showed that ZnFe 2 O 4 /rGO Nanocomposites could act as a readily available, eco-friendly, and cost-effective adsorbent to remove dyes from wastewater of various industries 18 .…”
Section: Introductionmentioning
confidence: 99%